2016
DOI: 10.1002/mana.201500481
|View full text |Cite
|
Sign up to set email alerts
|

Well-posedness of degenerate differential equations with fractional derivative in vector-valued functional spaces

Abstract: In this paper, we study the well‐posedness of the degenerate differential equations with fractional derivative Dαfalse(Mufalse)false(tfalse)=Aufalse(tfalse)+ffalse(tfalse),false(0≤t≤2πfalse) in Lebesgue–Bochner spaces Lpfalse(double-struckT;Xfalse), periodic Besov spaces Bp,qsfalse(double-struckT;Xfalse) and periodic Triebel–Lizorkin spaces Fp,qsfalse(double-struckT;Xfalse), where A and M are closed linear operators in a complex Banach space X satisfying D(A)⊂D(M), α>0 and Dα is the fractional derivative in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…We notice that the well-posedness of the equations (𝑃) was studied in [10] in the special case when 𝐹 = 0. Thus, our results also generalize the previous known results obtained in [4,5,8,9,15]. This paper is organized as follows.…”
Section: Introductionsupporting
confidence: 89%
“…We notice that the well-posedness of the equations (𝑃) was studied in [10] in the special case when 𝐹 = 0. Thus, our results also generalize the previous known results obtained in [4,5,8,9,15]. This paper is organized as follows.…”
Section: Introductionsupporting
confidence: 89%
“…More precisely, assuming that 1 < α ≤ 2 and X satisfy a geometrical hypothesis, in [22,Theorem 3.15] the authors showed that for all f ∈ L p 2π (R, X) there exists unique u ∈ H α,p 2π (R, X) ∩ L p 2π (R, D(A)) satisfying (1) if and only if {(im) α } m∈Z ⊆ ρ(A) and the set {(im) α (A + (im) α I) -1 } m∈Z is Rademacher bounded (or R-bounded). See also [3,Theorem 3.3] for the analogous result in the case 0 < α ≤ 1 and [5][6][7]18] for extensions of this result to more general models.…”
Section: Introductionmentioning
confidence: 80%
“…Therefore, we can conclude that GL D α t u N (t) + Au N (t) = f N (t) i.e. u N is a 2π -periodic solution of (5). Now, we study the convergence normal of the series.…”
Section: Definition 31mentioning
confidence: 96%
See 1 more Smart Citation